(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2025)
Background: Retroperitoneal fibroids are rare benign smooth muscle tumors accounting for approximately 1.2% of all uterine leiomyomas. Their atypical extrauterine location often leads to diagnostic uncertainty and may mimic pelvic malignancies. Minimally invasive and robotic-assisted surgical approaches have recently expanded therapeutic options for such complex cases. Case Presentation: A 49-year-old multiparous woman presented with heavy menstrual bleeding and dull pelvic pain for one year. Clinical examination revealed a firm, immobile mass in the rectovaginal septum. MRI identified a 7×6×5 cm retroperitoneal fibroid with degenerative changes compressing the rectum, along with two smaller uterine fibroids. Tumor markers were normal. The patient underwent robotic-assisted hysterectomy with concomitant myomectomy using the da Vinci Xi system. The retroperitoneal fibroid was safely dissected and delivered vaginally without intraoperative complications. Result: Postoperative recovery was uneventful, and the patient was discharged after 48 hours. Histopathology confirmed benign leiomyoma. At one-month follow-up, she remained asymptomatic. Conclusion: Robotic-assisted surgery provides enhanced visualization and precision, enabling safe removal of deeply impacted retroperitoneal fibroids with minimal morbidity. This case highlights the safety and efficacy of robotic-assisted management in complex gynecologic surgery.